1994
DOI: 10.2307/1591942
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Colonization and in vivo Expression of F1 (Type 1) Fimbrial Antigens in Chickens Experimentally Infected with Pathogenic Escherichia coli

Abstract: Escherichia coli strains that cause septicemia of poultry often possess F1 (type 1) fimbriae (encoded by pil [fim] homologous gene clusters) and/or P fimbriae (encoded by pap homologous gene clusters). These fimbriae are thought to be involved in infection and colonization. To study the dynamics of infection due to E. coli with different virulence determinant profiles and to examine the expression of these fimbriae in vivo, three pathogenic E. coli isolates--O1 (pil+/pap+), O2 (pil+/pap), and O78 (pil+/pap+)--… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 20 publications
2
39
0
Order By: Relevance
“…Escherichia coli is present in the normal intestinal flora of birds. Only some strains with specific virulence attributes, designated as avian pathogenic E. coli (APEC), are able to cause disease such as acute colisepticaemia, fibrinopurulent polyserositis, aerosacculitis, pericarditis, salpingitis, synovitis, omphalitis, yolk sac infection, swollen head syndrome, coligranuloma, and cellulitis (Vidotto et al ., 1990;Dozois et al ., 1994;Gomis et al ., 1997;Pourbakhsh et al ., 1997;Dho-Moulin & Fairbrother, 1999). Among the virulence factors involved in the pathogenesis of colibacillosis, F1 (type 1) fimbriae have been shown to adhere to chicken respiratory epithelial cells of the pharynx and trachea (Dozois et al ., 1994;Dho-Moulin & Fairbrother, 1999), Temperature-sensitive haemagglutinin (Tsh) plays a role in the colonization of air sacs (Dozois et al ., 2000), the aerobactin ironsequestering system allows E. coli growth in a low concentration of free iron in physiological liquids such as blood (Dho-Moulin & Fairbrother, 1999) and P fimbriae are important in the later stages of infection for the adhesion to internal organs (Dho-Moulin & Fairbrother, 1999), giving resistance to phagocytosis (Pourbakhsh et al ., 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Escherichia coli is present in the normal intestinal flora of birds. Only some strains with specific virulence attributes, designated as avian pathogenic E. coli (APEC), are able to cause disease such as acute colisepticaemia, fibrinopurulent polyserositis, aerosacculitis, pericarditis, salpingitis, synovitis, omphalitis, yolk sac infection, swollen head syndrome, coligranuloma, and cellulitis (Vidotto et al ., 1990;Dozois et al ., 1994;Gomis et al ., 1997;Pourbakhsh et al ., 1997;Dho-Moulin & Fairbrother, 1999). Among the virulence factors involved in the pathogenesis of colibacillosis, F1 (type 1) fimbriae have been shown to adhere to chicken respiratory epithelial cells of the pharynx and trachea (Dozois et al ., 1994;Dho-Moulin & Fairbrother, 1999), Temperature-sensitive haemagglutinin (Tsh) plays a role in the colonization of air sacs (Dozois et al ., 2000), the aerobactin ironsequestering system allows E. coli growth in a low concentration of free iron in physiological liquids such as blood (Dho-Moulin & Fairbrother, 1999) and P fimbriae are important in the later stages of infection for the adhesion to internal organs (Dho-Moulin & Fairbrother, 1999), giving resistance to phagocytosis (Pourbakhsh et al ., 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, the economic, public health and animal welfare significance of avian colibacillosis, has led to a number of studies from United States of America aiming to define APEC and to identify pathogenicity mechanisms (Jeffrey et al, 1999;Kariyawasam and Nolan, 2009;Norton et al, 2000). Studies have identified a large number of VGs in E. coli cultured from birds with avian colibacillosis (Antão et al, 2008;Dissanayake et al, 2014; and relevance of these VGs in the pathogenicity of avian colibacillosis is still poorly understood and the majority of studies on APEC and APEC-associated VGs are descriptive (Dozois et al, 1994;Jeffrey et al, 1999;Norton et al, 2000;Obeng et al, 2012;Zhao et al, 2009)…”
Section: Avian Pathogenic E Coli (Apec)mentioning
confidence: 99%
“…Both fimbriae types 1 and P adhere to tracheal epithelial cells of chickens (La Ragione et al, 2000;Yerushalmi et al, 1990). Type 1 fimbriae can be found on more than 70% of APEC cultured from the respiratory tract of birds with colibacillosis (Dho-Moulin and Fairbrother, 1999;Dozois et al, 1994;Janssen et al, 2001;Pourbakhsh et al, 1997). In contrast, P fimbriae were expressed by less than 30% of APEC strains that were colonising the respiratory system and internal organs (Pourbakhsh et al, 1997;Stordeur et al, 2004).…”
Section: F1 Fimbriae (Type 1 Pili)mentioning
confidence: 99%
See 1 more Smart Citation
“…The role of type 1 fimbriae in colibacillosis has been associated with mucus adherence and trachea and intestinal tract colonization (8,11,13,28,31,35). P fimbriae are mannose resistant hemagglutinating fimbriae present in E. coli strains causing urinary tract infections in humans and also may be expressed by some E. coli of avian origin.…”
Section: Introductionmentioning
confidence: 99%